Fish discard in artisanal fishery of shrimp (Litopenaeus vannamei and L. stylirostris) in the Mar Muerto coastal lagoon, Gulf of Tehuantepec, Mexico - Hernández-Roque, Jonny A. (2018)
Discarded ichthyofauna associated to unregulated artisanal shrimp fishery in the Mar Muerto coastal lagoon, Gulf of Tehuantepec, Mexico, was characterized. Shrimp catches were sampled from October 2017 to January 2018 with fixed cod-end nets. In this study, discard averaged 64.2 ± 15.3% of the total biomass captured, while fish amounted to 51% to 79.5% of this discard, with an estimated general ichthyofauna/shrimp ratio of 1.89: 1 kg. No relationship was found between shrimp catch and discard ichthyofauna biomass. High values of diversity are recorded in November and December due to a greater presence of marine organisms. It was shown that cod-end net fishing potentially affects at least 73 fish species, which, according to their average size and species (9.9 ± 9 cm, standard length), may be juvenile and sub-adult individuals. The families best represented in the fish list were Carangidae, Ophichthidae, and Gerreidae. Although a relatively high richness is reported in the discard, only 4 species were dominant. Fifteen new records of fish were added to the known ichthyofauna in the local and regional context. Further characterizations on by-catch and discards are necessary to propose management actions and reduction of the fishing impact.